Reconsidering rural land use and livelihood transition under the pressure of urbanization in Vietnam: A case study of Hanoi. (December 2020) - Nguyen, Quang; Kim, Doo-Chul
Highlights: Land acquisition for urbanization caused huge loss of farmland in suburban Hanoi, Vietnam. Land acquisition policy was accused of disrupting peri-urban livelihoods. This case study shows how this claim is misleading. An early livelihood transitions on the urban fringes, in which farmers found new means of livelihood because of urbanized factors. This early transition helped most local laborers prepare to move on from farming when land acquisition policies were implemented. Abstract: Over the last two decades, land acquisition for urbanization has caused a huge loss of farmland on the fringes of Hanoi, Vietnam. Previous studies have often criticized this policy for pushing farmers out of farming and disrupting peri-urban endogenous development. This study provides a case report of a peri-urban commune in western Hanoi to show how this claim is misleading. We found that livelihood transitions in this commune took place early on, and this helped most local laborers prepare to move on from farming when urbanization sped up and land acquisition policies were implemented. As a result, they were able to adapt to farmland loss without experiencing major difficulties and to transform their livelihoods for the better. This early transition was popular in the peri-urban context of northern Vietnam, where the inherent lack of employment and income from farming as well as the favorable location induced local laborers to go beyond the villages in pursuit of new opportunities. They actively took advantage of the changes around them to find new means of livelihood in order to earn higher incomes. This study calls for improvements in the compensation scheme and urban planning processes to make urbanization and land acquisition policies work for people on the fringes of cities in northern Vietnam.